Comparative Life Cycle Assessment of Chemical and Biocatalytic 2'3'‐Cyclic GMP‐AMP Synthesis. Issue 5 (12th December 2022) - Becker, Martin; Ziemińska‐Stolarska, Aleksandra; Markowska, Dorota; Lütz, Stephan; Rosenthal, Katrin
Abstract: Life cycle assessments (LCAs) can provide insights into the environmental impact of production processes. In this study, a comparative LCA was performed for the synthesis of 2'3'‐cyclic GMP‐AMP (2'3'‐cGAMP) in an early development stage. The cyclic dinucleotide (CDN) is of interest for pharmaceutical applications such as cancer immunotherapy. CDNs can be synthesized either by enzymes or chemical catalysis. It is not known which of the routes is more sustainable as both routes have their advantages and disadvantages, such as a poor yield for the chemical synthesis and low titers for the biocatalytic synthesis. The synthesis routes were compared for the production of 200 g 2'3'‐cGAMP based on laboratory data to assess the environmental impacts. The biocatalytic synthesis turned out to be superior to the chemical synthesis in all considered categories by at least one magnitude, for example, a global warming potential of 3055.6 kg CO2 equiv. for the enzymatic route and 56454.0 kg CO2 equiv. for the chemical synthesis, which is 18 times higher. This study demonstrates the value of assessment at an early development stage, when the choice between different routes is still possible. Abstract : Early assessment : For 2'3'‐cyclic GMP‐AMP (2'3'‐cGAMP) synthesis, a comparative life cycle assessment is performed for biocatalytic and chemical synthesis at an early development stage. An 18‐fold increase of global warming potential and other impact categories is determined for the chemical synthesis. Possible optimizations are examined for both synthesis routes with a sensitivity analysis.